An effective design of sun tracking system to increase the performance of solar cells - Lai, Weng Hong (2010)
Solar energy is the sun’s rays (solar radiation) that reach the earth. In tropical countries, solar energy potential in wide range of application for remote urban areas is growing rapidly. The major disadvantage of solar energy is the amount of sunlight that arrives at the earth’s surface is not constant. It depends on location, time of day, time of year and weather conditions. In addition, the sun doesn’t deliver that much energy to any exact place at one time, a large surface area is required to collect the energy at a useful rate. Most of the current technology applies only static solar cells that cannot response to the actual instant position of the sun for maximum sun shine. The objective of this work is to design an effective Sun Tracking System that would increase the performance of Solar Cells. In this research, the compartments considered for the proposed system are Solar Cells, Moving Mechanism and Stepper Motor that will be controlled based on the detector of the sun shine using web-camera. As soon as the sun can be tracked, the voltage, current and power received will always be at the maximum efficiency. This research could provide significant improvement in alternative energy as seen from the results which are given in this thesis